Integrated Marketing Communication For L'Oreal Paris Revitalift - Riady, Indra; Wibowo, Satya Aditya (The Indonesian Journal of Business Administration, 2014)
Abstract– Revitalift from L’Oreal Paris as one of the player in women anti-ageing skincare market has a goal of their marketing activities to achieve marketing effectiveness. Performance of L’Oreal Paris Revitalift was decreased since 2010 to 2012, shown by the low market share of Revitalift in Indonesia women anti-ageing skincare market. Performance also had impact to the revenue that Revitalift received, sales of Revitalift product also decreased since 2010 to 2012. The performance that have targeted by the company both market share and sales was not achieved in three consecutive years. Increasing market share, company have to push five factors, one of the factor is awareness. L’Oreal Paris Revitalift is not top of mind brand in Indonesia women anti-ageing skincare market, it shown by TOPBRAND index that Revitalift has the lowest score than the competitor such as Pond’s and Olay. Awareness is related with marketing communication strategy as way to introduce and communicate the brand to the target market. Marketing Communication is one of the ways to create awareness among audience. This paper focus to analyze Revitalift consumer channel preferences of marketing communication channel.  Cluster analysis use to grouping the respondent, discriminant used for analyze the most potential channel that choose by consumer. Completing the analysis, in this paper also use recommendation score as a method to evaluate marketing channels role analysis based on brand management theory. Two main objectives of the integrated marketing communication (IMC) activities are increasing product awareness and increasing purchase intention. This paper focus in strategy and tactics on media mixes that will use for Revitalift and also propose new budget allocation for media use based on result of consumer preference. The strategy will be implemented for a whole year of 2014. Based on strategy and tactics Revitalift will use all the communication channels that already have and some of sales distribution channel also will be empowered to maximize the result of marketing communication objective. Keywords: Integrated Marketing Communication, Marketing Communication Effectiveness, L’Oreal Paris Revitalift, Awareness, and Market Share.